Decision Criteria For Assessment Of Contractors In Prequalification Phase Of Public Projects - Ali Raza Khoso*,Nafees Ahmed Memon, Samiullah Sohu, Fida Siddiqui, Jam Shahzaib Khan (International Journal of Advanced Science and Technology, 2020)
Prequalification decisions are often cumbersome to construction client and often proved vague and dissimilar in many situations in public projects in Pakistan. Reviewing the process unfolded various deviations in public departments of the country as there are no single specific decision criteria available to cope with this basic issue of the construction sector. This research aims to points out the most suitable criteria for the pre-qualification process for Pakistan construction projects. The critical analysis of contemporary methods opted by public departments is also a part of this research. The data has been gathered through interviews and floating several questionnaires. Descriptive analysis is done by using computer software, i.e. MS Excel & SPSS. The ranking of criteria & sub criteria has been decided based on Relative Importance Index (RII) & Average Index (A.I) values respectively. The research findings divided the decision criteria among eight (08) major criteria & forty-five (45) sub criteria by critical and in –depth reviewing of procurement guidelines,discussions with the experts of public departments, professionals, procurement &contract officers and CEO of various firms. The critical review of current status of prequalification revealed various contradictions in the current practices. The research concludes that the major prequalification criteria are; experience and past performance, financial stability, personnel capabilities, equipment capabilities and managerial capabilities. However, the other criteria were also incorporated such as health & safety, past relationships & geographic location of contractor. The research recommends the identified criteria in taking prequalification decisions in tendering stage.